2015
DOI: 10.18172/cig.2703
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods to measure soil erosion in the Central Ebro Valley

Abstract: ABSTRACT. Fire is a natural factor of landscape evolution in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
6
0
1
Order By: Relevance
“…The experimental observations verified the successful efficacy of the wood strands in reducing runoff, soil loss, and sediment concentration (almost significant at p value <.05) through increasing the soil water retention and soil protective cover. Similar results were reported for different soil amendments applications specifically wood‐based mulches (e.g., León et al, ; Prosdocimi et al, ; Turk, ). The three‐dimensional layering of the wood strands provided a highly stable matrix (Yanosek et al, ) leading to soil stabilization against rainfall and runoff.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The experimental observations verified the successful efficacy of the wood strands in reducing runoff, soil loss, and sediment concentration (almost significant at p value <.05) through increasing the soil water retention and soil protective cover. Similar results were reported for different soil amendments applications specifically wood‐based mulches (e.g., León et al, ; Prosdocimi et al, ; Turk, ). The three‐dimensional layering of the wood strands provided a highly stable matrix (Yanosek et al, ) leading to soil stabilization against rainfall and runoff.…”
Section: Discussionsupporting
confidence: 87%
“…It is revealed that 40–80% ground cover of agricultural straw and wood shred could effectively protect the soil against negative effects of fire. León, Badía, and Echeverría () found that wood chip mulch reduced both runoff rate (from 9.39 to 4.36 mm hr −1 ) and soil loss (3.82–1.92 g m −2 ) by at least half when applied to burnt soils is northeastern Spain. Additionally, Prats, Abrantes, Crema, Keizer, and de Lima () tested eucalypt bark strands mulch in three strip lengths of 0.9, 1.8, and 2.7 m with two cover percentages of 50 and 70.…”
Section: Introductionmentioning
confidence: 99%
“…Bedrock in the Ebro valley area (Zuera) is formed by Miocene limestones and gypsum, and soils are Rendzic Phaeozem, Leptic and Haplic Gypsisol León et al, 2015a). The greatest soil diversity is found in the Pyrenees area (Jaca), with Kastanozem, Phaeozem, calcic Regosol, Leptosol or Cambisol, and bedrock is composed of Eocene Flysch turbidites in the Pyrenean mountain range and Eocene marls in the Inner Pyrenean Depression Lana-Renault et al, 2011).…”
Section: Study Areamentioning
confidence: 99%
“…Despite of the real and long term value of these measurements, many of them have been dismantled during the last decades, leading to a lack of measured values of soil erosion (Stroosnijder, 2005). This trend has been inverted during the last decade, where different types of plot systems have been installed (e. g. Bagarello et al, 2013, García-Orenes et al, 2010, 2009León et al, 2015;Rodrigo-Comino et al, 2015, 2016Todisco et al, 2012). The investigation by Kirchhoff et al (2017) included in this special issue takes over the need to gain realworld data on soil erosion, combining plot measurements with rainfall simulations.…”
Section: Experiments In Geomorphologymentioning
confidence: 99%